PREDICTION OF LOCALIZED INFLAMMATORY PERIODONTAL TISSUE DISEASES IN YOUNG PERSONS - O.V. Kholodnyak (Український стоматологічний альманах, 2018)
Periodontal diseases are among the diseases that are known from ancient times. Their prevalence has increased dramatically with the progress of civilization. At present the problem of prevention and treatment of periodontal diseases is presented in many domestic and foreign studies. Therefore, the strategy of prevention of these diseases should be based on the concept of risk factors. However, the issue of forecasting, prevention and treatment of periodontal tissue diseases by the action of local damaging factors has not been sufficiently studied.